Unlocking the potential of hydrogen deuterium exchange via an iterative continuous-flow deuteration process - Kevin Tatoueix; Marco Lepron; Cédric Barboux; Marie-Christine Scherrmann; Grégory Pieters; Sophie Feuillastre (Nature Communications)
Abstract Labelled compounds bearing hydrogen isotopes are keystones in diverse areas constituting a multi-billion dollar global market including drugs, diagnostics, biology, toxicology and smart materials. While hydrogen deuterium exchange (HDE) methods hold promise as relevant tools for the late-stage and one-step preparation of deuterium-labelled compounds, they often fall short in achieving sufficient isotopic purity combined either with a site-selectivity or with a full deuteration process, highlighting the need for further development and optimisation. This report pinpoints an approach to unlock the potential of HDE using the concept of iterative runs in continuous-flow technology (recirculation process). This closed-loop process grants access now to deuterated compounds with high isotopic purities, labelled at a precise site or perdeuterated on demand, in a fast, productive, and environmentally friendly way.